2004
DOI: 10.2202/1548-923x.1044
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Music-making: An Integrative Group Intervention for Reducing Burnout and Improving Mood States in First Year Associate Degree Nursing Students: Insights and Economic Impact

Abstract: The challenges of providing exemplary undergraduate nursing education cannot be underestimated in an era when burnout and negative mood states predictably lead to alarming rates of academic as well as career attrition. While the multi-dimensional nature of this complex issue has been extensively elucidated, few rational strategies exist to reverse a disheartening trend recognizable early in the educational process that subsequently threatens to undermine the future viability of quality healthcare. This control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 25 publications
5
79
0
Order By: Relevance
“…1981, Mancini et al. 1983, Severtsen & Bruya 1986; Forbes & Pekala 1993, Bittman et al. 2004, Consolo et al.…”
Section: Resultsmentioning
confidence: 99%
“…1981, Mancini et al. 1983, Severtsen & Bruya 1986; Forbes & Pekala 1993, Bittman et al. 2004, Consolo et al.…”
Section: Resultsmentioning
confidence: 99%
“…RMM focuses on personal expression and group support, rather than mastery and performance [14]. Research has shown that RMM activities are effective bio-behavioral modulators for reducing stress, limiting occupational burnout and attrition, and enhancing quality of life [15,16]. Although acute psychological stress has been shown to induce changes in signaling cascades, cellular defense mechanisms, and peripheral blood gene expression, little is known about molecular responses that accompany relaxation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The following is a summary of the rationale underlying HEP: In four areas, we will help you develop new habits and reinforce new ones that are known to increase well-being: (1) Physical activity enhances one’s sense of well-being, increases energy, and reduces health risks, including coronary heart disease, stroke, colon cancer and diabetes; (2) Functional movement improves posture/core strength, balance, agility and joint mobility, resulting in a physically more resilient individual less prone to sustain injury from spontaneous or unpredictable events; (3) Supportive Music and Imagery and other elements of music therapy generate positive emotions to facilitate performance on concrete tasks and is used in a group setting to create a common experience, thereby increasing relaxation-related melatonin levels (Kumar et al, 1999), enhancing immune response (Bittman et al, 2001; Wachi et al, 2007), favorably changing stress-related gene expression (Bittman et al, 2005), increasing positive mood and reducing burn out (Bittman et al, 2004); (4) Incorporating evidence-based nutrition into one’s eating lifestyle will help reduce the risk of cardiovascular disease, hypertension, dyslipidemia, type 2 diabetes, overweight and obesity, osteoporosis, constipation, diverticular disease, iron deficiency anemia, oral disease, malnutrition, and some cancers (U.S. Department of Health and Human Services and U.S. Department of Agriculture, 2005).…”
mentioning
confidence: 99%